PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IV SDN 014 PUTAT KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Busrial '; Mahmud '; Lazim.N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to find out whether the Implementation of Problem Based learning Model can improve social science learning results of class IV students in SD Negeri 014 Putat Kecamatan tanah Putih Kabupaten Rokan Hilir. The type of this research in classroom action research (CAR) with the research subjects are class IV students which amounts to 24 students. The data collection techniques used is tests, observation, observasi and documentation. The research concludedthat social science learning which using problem based learning can improve the teacher’s activity, student’s activity and social learning result. At the first meeting of cycle I, the teacher’s activity percentage was 60% and categorized enough, at the second meeting the percentage increased to be 70% categorized good. Then for cycle II at the first meetingthe percentage was 80% and categorized good, at the second meeting the percentage was 95% and categorized very good. Then for student’s activity cycle I at the first meeting the percentage was 35% and categorized deficient and the second meeting the percentage was 60% and categorized enough. For the first meeting of cycle II the percentage was 70% categorized good, at the second meeting the percentage was 95% and categorized very good. The student’s social science learning result from the average grades before actions (basic score) was 60,25 increased at cycle I to be 72,50 with the percentage increase by 20,33% and at cycle II the average grades increased to be 82,13 with the percentage increase by 36,31% from the basic score by 60,25.Keywords: Problem Based Learning Model (PBL). Learning result